Research on the Characteristics of Uncertainty of China's Economic Policy - Liu, Ting; Lv, Rongxia (Journal of Accounting, Business and Finance Research, 2019)
As a socialist country, China has made great progress in its economy since the implementation of the reform and opening-up policy in 1978. Economic policy plays an important role in economic development. But with the arrival of the new normal economy, slow development has become the main problem facing us now, even the downward pressure of the economy. Therefore, the Chinese government constantly adjusts its economic policies to adapt to the development of the economy. Appropriate changes in economic policies are conducive to better play the role of adjustment, but frequent changes in policies will hinder the development of the economy to a certain extent. This paper analyses the characteristics of China's EPU index tries to find the characteristics of the index and puts forward some policy recommendations. By using the GARCH model to analyze China's EPU index, we find that the index has the following characteristics: volatility clustering, autocorrelation and heteroscedasticity. And through the trend chart of the index, we can see that in recent years, China's EPU index has been improving in general.